In vitro susceptibility of isolates of Brucella from man and animals to antibiotics - SINGH, D K; GOSWAMI, T K (The Indian Journal of Animal Sciences, 2014)
In vitro susceptibility of 37 clinical isolates of Brucella from man and animals to conventionally recommended antibiotics pfloxacin, ofloxacin and ciprofloxacin and azithromycin was determined. While most of the isolates were highly sensitive to rifampicin, doxycycline and co-trimoxazole, a moderate degree of sensitivity was noted to streptomycin, tetracycline and gentamicin. Among the quinolones, maximum susceptibility was observed for ciprofloxacin followed by of loxacin and pfloxacin. Rifampicin could not eliminate brucellae up to 36 hr in vitro suggesting the longer therapy consistent with the recommended long regimen of treatment.